Ideologia e poder no agendamento do discurso polifônico da imprensa em relação à seca no nordeste - Rosado, Cid Augusto da Escóssia (2008)
This dissertation work is an effort to understand how the ideology and the power interferes in the signification of the speeches immersed in the context of the printed media concerning the drought in the Northeast of Brazil, weather occurrence that punishes 23 million of Brazilians, with all sort of problems. It also has specific concern about the everyday usage of the language and with the routines of the information production, without losing of sight the role of History in the formation of the identity of individuals and people. The research work is also developed in an interdisciplinary environment, applying to the formed corpus five articles from Folha de São Paulo , collected from January to July of 2005, the French Analysis method of the Speech and the theory of the polyphony of Bakhtin, in the Applied Linguistics area, accomplished with Communication beddings as the agenda-setting. The results ended to a good understanding about the ideology and power´s influence and chaining in the speeches formations as well as to comprehend peoples concept in an environment of almost-mediated interaction, bringing a media look about polyphony in the bakhtinian mold, besides showing how all these questions interferes with the half-barren the Northeast media´s vision on the subject